Reward-based plasticity of spatial priority maps: Exploiting inter-subject variability to probe the underlying neurobiology. Issue 2 (3rd April 2017) - Della Libera, Chiara; Calletti, Riccardo; Eštočinová, Jana; Chelazzi, Leonardo; Santandrea, Elisa
ABSTRACT: Recent evidence indicates that the attentional priority of objects and locations is altered by the controlled delivery of reward, reflecting reward-based attentional learning. Here, we take an approach hinging on intersubject variability to probe the neurobiological bases of the reward-driven plasticity of spatial priority maps. Specifically, we ask whether an individual's susceptibility to the reward-based treatment can be accounted for by specific predictors, notably personality traits that are linked to reward processing (along with more general personality traits), but also gender. Using a visual search protocol, we show that when different target locations are associated with unequal reward probability, different priorities are acquired by the more rewarded relative to the less rewarded locations. However, while males exhibit the expected pattern of results, with greater priority for locations associated with higher reward, females show an opposite trend. Critically, both the extent and the direction of reward-based adjustments are further predicted by personality traits indexing reward sensitivity, indicating that not only male and female brains are differentially sensitive to reward, but also that specific personality traits further contribute to shaping their learning-dependent attentional plasticity. These results contribute to a better understanding of the neurobiology underlying reward-dependent attentional learning and cross-subject variability in this domain.